Epicuticular wax of sweet sorghum influenced the microbial community and fermentation quality of silage - Tang, Wei; Liao, Longxing; Xiao, Yu; Zhai, Jianrong; Su, Hang; Chen, Yingjie; Guo, Yanjun (Frontiers in Microbiology, 2022)
Epicuticular wax, as secondary metabolites (hydrophobic compounds) covering plant surface, plays important roles in protecting plants from abiotic and biotic stresses. However, whether these compounds will influence fermentation process of silage is still not clear. In this study, two sweet sorghum cultivars with varying epicuticular wax on sheath (bloom), Yajin 2 (YJ, less bloom) and Jintian (JT, dense bloom), were harvested at flowering and maturing stages, and ensiled with or without bloom, aiming to evaluate the effects of bloom on fermentation quality, feed nutrition and microbial community. The bloom was collected manually with de-waxed cotton and extracted with chloroform. The results showed that the bloom reduced the concentrations of water-soluble carbohydrate and crude protein of the two cultivars at both stages, reduced lactic acid (LA) for YJ at both stages and for JT at flowering stage, and increased LA for JT at mature stage. The α-diversity of bacterial communities of the silage fermentation with bloom was significantly lower than that without bloom. Bloom increased the abundance of Lactobacillus, reduced that of Bacillus and Weissella, and significant correlations were observed between fermentative qualities and bacterial abundances. However, decreased diversity of bacterial community and the contents of LA implied that shifts in bacterial community might exert negative effects on silage fermentation. Our results suggest that bloom wax could alter the microbial community composition of ensiled sweet sorghums, which thus influence the fermentation qualities.